ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU MAHASISWA DALAM MEMILIH PERGURUAN TINGGI DI PALEMBANG ATAU INDRALAYA DENGAN METODE CHAID (Studi pada Fakultas Ekonomi Universitas Sriwijaya) - zakaria Wahab; Yuliansyah M. Diah (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2010)
This paper aims to investigate the factors that have influence on the student of economic choice to attend the graduate school on Palembang campus or Indralaya campus. The data was collected through a structured questionnaire with regard to student’s perceive on the independent variable in this research such as security, culture, reference, tuition fee, quality, promotion, and location. Total of 120 students participate in this study that consist of 60 economic students of Indralaya campus and 60 economic students of Palembang campus.The empirical result in thi study reveal that there is a significant relationship between independent variable such as security, gender, and reference and student’s choice to attend the campus. However, there are some dimensions which are significantly had strong relationship such as variable entertainment, popularity, and tuition fee. One variabel which is not influence the relationship between independent variable and campus choosing is variable quality.Overall, the findings of the present research indicate that there are some factors which are affect student to choose either Indralaya campus or Palembang campus.Key words: student behavior, graduate school, Indralaya campus, Palembang campus, South Sumatera, Indonesai.